2013
DOI: 10.1111/acem.12052
|View full text |Cite|
|
Sign up to set email alerts
|

Unscheduled Return Visits to the Emergency Department: Consequences for Triage

Abstract: Objectives: The objective was to conduct a survey of unscheduled revisits (URs) to the emergency department (ED) within 8 days of a prior visit, to test the hypothesis that patients making these URs are disproportionately likely to suffer short-term mortality or manifest a need for any admission to the hospital (adverse events [AEs]) at the time of the UR, compared to patients triaged at the same level who did not have an unscheduled ED revisit within 8 days.Methods: This was a 1-year retrospective study of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 27 publications
7
33
2
Order By: Relevance
“…Only one study has been performed in Italy to the best of our knowledge, and was mainly focused on evaluating resource utilization in management of AAP (19). The scarce information available so far is particularly concerning if one considers that abdominal pain represents one of the leading causes of repeated ED visits, often necessitating additional and expensive testing, and sometimes plagued by unfavorable outcomes (20)(21)(22)(23). Therefore, the aim of this study was to investigate the epidemiology of AAP in an adult patient population admitted to a large urban ED and, even more importantly, to analyze the clinical outcomes based on patients returning to the ED within 5 and 30 days after first admission and needing surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study has been performed in Italy to the best of our knowledge, and was mainly focused on evaluating resource utilization in management of AAP (19). The scarce information available so far is particularly concerning if one considers that abdominal pain represents one of the leading causes of repeated ED visits, often necessitating additional and expensive testing, and sometimes plagued by unfavorable outcomes (20)(21)(22)(23). Therefore, the aim of this study was to investigate the epidemiology of AAP in an adult patient population admitted to a large urban ED and, even more importantly, to analyze the clinical outcomes based on patients returning to the ED within 5 and 30 days after first admission and needing surgery.…”
Section: Introductionmentioning
confidence: 99%
“…While unscheduled return visits to the ED within 72 h are commonly used as a trigger to find these errors,11 12 evidence suggests that the revisits associated with poor quality and error may occur up to 9 days after the initial visit 13. Reviews of unscheduled ED return visits estimate that 12%–25% of patients returning had an incorrect initial diagnosis 14 15…”
Section: Introductionmentioning
confidence: 99%
“…While several reviews of return visits have found abdominal pain to be a major factor associated with unscheduled returns (n=10),15 prior studies of repeat visits to the ED and adverse events have only focused on chest pain (n=13), psychiatric complaints (n=10) and chronic lung disease (n=8). Abdominal pain is the most common chief complaint16 and also a particular area of risk for the ED physician because several abdominal conditions can present with uncommon or unusual presentations.…”
Section: Introductionmentioning
confidence: 99%
“…Per cutaneous coronary catheterization (PCI) within 90 min in ST elevation myocardial infarction (STEMI) [4] Preventive aspirin therapy for patients with acute MI [5] Preventive statins therapy for patients with acute MI [6] Performance evaluation of risk of stroke in patients with atrial fibrillation [7] Evaluation of Padua score for prevention of venous thrombosis [8] Carotid arteries duplex within 72 h of admission to the emergency department due to transit ischemic attack [9] TPA or neuro-angiography after acute CVA [10] Preventive antibiotic treatment an hour before colectomy [11] Operation of hip fracture within 48 h of admission [12] Antibiotic prophylaxis before hip surgery [13] Preventive antibiotic treatment before Cesarean section [14] Preventive anti-thrombotic treatment before hysterectomy [15] Steroids therapy for women at risk of preterm delivery [16] Hospitalization within two weeks after gynecologic elective surgery [17] Hospitalization within two weeks after elective cesarean section [18] Readmissions to the emergency department within 24 h [19] Computing diagnosis in the emergency department, brain CT or MRI in acute CVA within 25 min of arrival to the emergency department [20] Chest x-rays interpretation NA Central line associated bloodstream sepsis (CLABSI) for 1,000 catheter-days [21] Clostridium difficile incidence for 1,000 hospitalization days [22] Falls for 1000 hospitalization days [23] Falls with severe damage for 1000 hospitalization days [24] Acquired pressure sore [24] Computing main diagnosis in the digital patient's file NA Longer hospitalization of more than 8 days following colectomy for colorectal cancer [25] Readmission within 2 weeks after trans urethral prostatectomy [26] Planned patient's discharge NA…”
Section: Indicator Referencesmentioning
confidence: 99%